Fractal Dimension Approach for Clustering of DNA Sequences Based on Internucleotide Distance - Sadikin, Mujiono; Wasito, Ito; Veritawati, Ionia (Proceeding Information Technology, 2013)
Abstract â Recently, the volume of biological data increasesexponentially. Problem of utilization of this kind of data is notonly concerning to the volume but also to its various format andstorage distribution. To solve this kind of problems, someapproaches require new methods, algorithms or tools to assisthuman being in getting beneficial from the biological data. Thispaper presents the usage of fractal dimension approach based oninter nucleotide distance to cluster DNA sequences. Internucleotide distance is a numerical representation of DNAsequences which is transformed to time series signal spectrum.Higuchi Fractal Dimension (HFD) is one of methods to estimatefractal dimension which it can be utilized to reduce time seriesdimension. HFD estimation then is applied to the signal spectrumand it is treated as input to clustering method. The result of thisclustering shows that HFD approach can be considered as analternative method for dimensional reduction purposes.Compared with previous study result as ground truth, the HFDapproach clustering provides some similarities in certain degree.Tested with two kinds of data test sample, this approach results 6and 7 group similarities of 10 groups.Â Keywords: DNA Sequences, Fractal, Inter Nucleotide Distances